2018
DOI: 10.1039/c7ob03025h
|View full text |Cite
|
Sign up to set email alerts
|

Formal total synthesis of salvianolic acid N

Abstract: An efficient synthetic pathway for the total synthesis of salvianolic acid N has been reported. The key reaction steps, the Wittig reaction for Z-stereoselectivity and an intramolecular cyclization for a seven membered ring skeleton, have been optimized to improve the synthetic feasibility and provide the best conditions in terms of yield. Moreover, a notable reaction is the reaction of the deprotected allylic group with Pd catalyst. An improved overall yield of 11% has been achieved for salvianolic acid N sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Wu et al in 2018 reported an efficient way for the synthesis of dibenzoxepine analog 145 as precursor of salvianolic acid N 150 . [ 82 ] Z ‐olefination via stereoselective Wittig reaction, copper‐catalyzed intramolecular Ullmann cyclization, and Heck coupling reaction with methyl acrylate were described as key reaction steps of this synthetic pathway (Scheme 44). In this synthesis, CuI was first used as a catalyst, but when Cu(OTf) 2 was used instead of CuI, the reaction efficiency was significantly increased.…”
Section: Copper‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…Wu et al in 2018 reported an efficient way for the synthesis of dibenzoxepine analog 145 as precursor of salvianolic acid N 150 . [ 82 ] Z ‐olefination via stereoselective Wittig reaction, copper‐catalyzed intramolecular Ullmann cyclization, and Heck coupling reaction with methyl acrylate were described as key reaction steps of this synthetic pathway (Scheme 44). In this synthesis, CuI was first used as a catalyst, but when Cu(OTf) 2 was used instead of CuI, the reaction efficiency was significantly increased.…”
Section: Copper‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…The benzoxepin salvianolic acid N (25) was isolated from Danshen, the dried root and rhizome of Salvia miltiorrhiza Bunge (Scheme 4). 7 Danshen is a traditional Chinese drug used for the treatment of coronary artery disease and is known to possess antiviral, antioxidant, and antitumor activities. The reported total synthesis began with aldehyde 20, which was converted into bromide 21 via bromination and tosyl- In 1991, Castedo reported the synthesis of norsecosarcocapnine (29), which also gave access to secosarcocapnine (30) via an intramolecular Ullmann coupling (Scheme 5).…”
Section: Oxepin Natural Productsmentioning
confidence: 99%
“…Racemic senoxepin (11), a norsesquiternelactone found in Senecio platyphylloides, was the first oxepin-containing natural product obtained by total synthesis by Bohlmann in 1989 (Scheme 2). 5 Starting from methyl 3,5-hexadienoate (7), epoxide 8 was synthesized in 14 steps. Allylic bromination of 8 with azobisisobutyronitrile (AIBN) and N-bromosuccinimide (NBS) produced the dibromide 9, which was directly subjected to Finkelstein conditions resulting in diene 10.…”
Section: Oxepin Natural Productsmentioning
confidence: 99%
“…Fortunately, this synthesis process does not have to go through the long synthesis and degradation pathway of SA-B in living system. Other synthesis approaches of salvianolic acid derivatives have also been postulated [ 24 , 25 , 26 ]. From the biological point of view, both for purified compounds and plant-based drug preparations, SA-A and SA-B are the most important and hence emphasis is given in this review to highlight their effect in the dementia brain.…”
Section: Natural Occurrence and Biosynthesis Of Rosmarinic And Salmentioning
confidence: 99%